Comparative Study of Onlay Versus Sublay Meshplasty in Ventral Hernia Repair: A Randomised Controlled Study - KUMAR, MANISH; SAWARKAR, PRASHANT; Saxena, Divish; SHERKAR, NITIN; DUBHASHI, SIDDHARTH (International Journal of Innovative Research in Medical Science, 2024)
Background: Ventral hernia is the commonest complication post laparotomy. As the spectrum of repair ranges from different techniques of open as well as laparoscopic, the optimal approach for abdominal ventral hernias is customized from patient-to-patient basis. This study is restricted to open ventral hernia repairs and it aims to compare Onlay with Sublay techniques for uncomplicated ventral hernias. Materials & Methods: This is a randomised control study that included 56 patients of uncomplicated ventral hernias, where patients were allocated into two groups of Onlay & Sublay techniques equally. Both the groups were comparable in terms of Age, Gender, BMI and size of defect to avoid selection bias. Results: 56 patients were included in the study with 28 patients in each group. The mean age& gender in both groups were comparable. The location of defect was found at umbilical region in 75.1% patients. The mean size of defect in group A & group B was 2.27cm & 2.34cm respectively. The mean operative time for Onlay meshplasty was 70.35 minutes as compared to 86.14 minutes for Sublay meshplasty which was statistically significant (p-value 0.0001). 10 patients (17.8%), with 7 patients belonging to Onlay group and 3 patients under Sublay group developed superficial SSI. No patient had mesh rejection, seroma formation or recurrence in the follow up period of one year. Conclusion: The different parameters compared for both the techniques in form of post-operative pain, length of hospital stays, development of SSI, seroma formation and incidence of recurrences were found to be insignificant. Therefore, we can conclude that neither of the technique proves superior to each other. The choice remains with operating surgeon, institutional or departmental policies and patient’s relevant anatomy related to hernial sac, defect size and location.